Синтез схем гидропневмоавтоматики - Черкашенко, Михаил Владимирович (НТУ "ХПИ", 2011)
Representation of the method of undivided decomposition of equations developed by the author in the modern edition considering last development, and allowing to synthesize minimal on quantity of elements and modules of the scheme of hydraulic and of pneumatic systems controls.
Keywords: гидропневмоавтоматика; построение схем; безраздельная декомпозиция